"Living Statues" and Nonuments as "Performative Monument Events" in Post-Socialist South-Eastern Europe. Issue 3 (15th May 2023) - Preda, Caterina
Abstract: After the fall of the socialist regimes in South and Eastern Europe socialist statues and monuments were either removed, dislocated, or resignified. Several performance practices have been employed to engage with these statues and monuments. Focusing on the role played by artistic memorialization in the processes of dealing with the communist past, this article uses the concepts of "performative monuments" (Widrich) and "memory events" (Etkind) to analyze several examples of what can be called "performative monuments events." As many statues were removed, the statues witnessed performative practices in the process of their elimination. The monuments that were conserved were dislocated and exhibited as part of "sculpture park museums" and observed nostalgic, ironic practices of tourists that perform the memory of communism by interacting with the monuments. This article analyzes several examples in Albania, Bulgaria and Romania of socialist monuments that have remained in place or that have been dislocated and resignified by contemporary artists using performative practices of memory events that engage monuments. This exploratory research argues that artists, through their "performative monuments events, " try to bring the people back to replace the statues with "living statues" and to question the absurd megalomaniac monuments using metaphorical, material instruments.